Incidence of occupational contact dermatitis in healthcare workers: a systematic review. (12th February 2021) - Larese Filon, F.; Pesce, M.; Paulo, M.S.; Loney, T.; Modenese, A.; John, S.M.; Kezic, S.; Macan, J.
Abstract: Healthcare workers (HCWs) can be considered at an increased risk of developing occupational contact dermatitis (OCD) due to repetitive hand washing with soaps and disinfectants and extended use of gloves for many hours during the day. The aim of this study was to summarize the incidence of OCD in HCWs. We searched the databases PubMed/MEDLINE (1980‐present), EMBASE (1980‐present) and Cochrane Library (1992‐present) through May 2020 using the search term 'incidence of contact dermatitis in HCWs' according to Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines. Overall, 16 studies (six cohorts; 10 register‐based) with follow‐up periods between 1987 and 2013 fulfilled the inclusion criteria. The incidence of OCD reported in studies using registers of occupational diseases ranged from 0.6 to 6.7 per 10 000 person‐years. The cohort studies reported incidence from 15.9 to 780.0 per 10 000 person‐years; the incidence was higher in studies which included apprentice nurses. A higher incidence was also observed amongst dental practitioners, particularly dental technicians and nurses, compared to other HCWs. Studies reporting incidence data are very scarce and results differed by study design, type of contact dermatitis and investigated HCWs. Our study highlighted the dearth of high‐quality data on the incidence of OCD and the possible underestimation of disease burden. Prospective cohort studies with harmonized designs, especially exposure assessment and outcome ascertainment, are required to provide more accurate, valid and recent estimates of the incidence of OCD. A high incidence amongst specific occupational groups suggests the need to undertake intervention studies with a focus on prevention, particularly during pandemics such as COVID‐19.